Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan (Studi Pada PT. Ultra Teknologi Indonesia) - Adik Ayu; Wenny Desty Febrian (CV. Multi Kreasi Media, 2023)
This study aims to analyze the effects of work discipline on employee performance, work motivation on employee performance, work environment on employee performance, and job satisfaction on employee performance. As well as work discipline, work motivation, work environment, and job satisfaction on employee performance at PT Ultra Teknologi Indonesia. This type of research is quantitative, with a saturated sample of all employees of PT Ultra Teknologi Indonesia totaling 50 employees. The analytical tools used are multiple linear regression, the t test, the F test, and the coefficient of determination (R2). Based on the results obtained, work discipline variables have no effect on employee performance. Work motivation variables have no effect on employee performance. Work environment variables have no effect on employee performance. Job satisfaction variables affect employee performance. The results of the F test analysis show that the variables of work discipline, work motivation, work environment, and job satisfaction together have an influence on employee performance.